Determination of lysine, tryptophan and protein in germinated of creole and QPM maize - García Rodríguez J. Guadalupe; Cervantes Ortiz, Francisco; Ramírez Pimentel Juan Gabriel; Aguirre Mancilla, Cesar; Rodríguez Perez Gilberto; Ochoa, Francisca; Mendoza Elos, Mariano (Revista Mexicana de Ciencias Agrícolas, 2017)
The objective of this research was to determine the lysine, tryptophan, protein and yield of green fodder in maize QPM and creole. The research was carried out at the CINVESTAV and Technological Institute of Roque, Celaya, México, in 2014. Two maize genotypes, one with high protein content (QPM) and a normal one, were evaluated. The production of green fodder was carried out according to the FAO method (2001). Samples were taken at 9, 11, 13, 15, and 17 days after sowing and seedling height, fresh weight, dry matter, lysine, tryptophan, protein and forage yield were taken as variables. The yield of green fodder reached its highest values at 17 days, creole 25.4 kg m-2 and QPM 27.14 kg m-2. For the lysine and tryptophan content the highest value was determined at 13 days in both genotypes, 0.55 and 1.17% and 1.18 and 0.56%, respectively. It was also concluded that the QPM maize protein was higher at 17 days with a value of 19.86% and for creole maize at 15 days with 14.45%.